Pengaruh Elektroplating Ni-Cr terhadap Wetability dan Ketahanan Korosi Sumuran pada Baja Tahan Karat 316L dalam Media Infus 0,9% NaCl - Binsar Maruli Tua Pakpahan; Muhammad Nuh Hudawi Pasaribu; Lisnawaty Simatupang; Robert Silaban; Natal Toga Hot Tua Pakpahan; Prada Sihombing; Sabas DK Sinaga (CV. IRA PUBLISHING, 2025)
This study aims to evaluate the effect of Ni-Cr electroplating on wettability characteristics and pitting corrosion resistance of 316L stainless steel in 0.9% NaCl infusion media. The electroplating process consisted of a nickel base coating for 15 minutes, followed by chromium plating with durations ranging from 10 to 22.5 minutes. Contact angle measurements showed that Ni-Cr coating increased the contact angle from 71.25° to 86.77°, indicating a surface transformation from hydrophilic to more hydrophobic. This increase in contact angle demonstrates the effectiveness of Ni-Cr plating in enhancing the material’s resistance to liquid penetration, a critical property for biomedical applications. Corrosion tests revealed a reduction in pit count and depth after plating, suggesting a significant improvement in resistance to localised corrosion. These findings indicate that Ni-Cr electroplating significantly improves pitting corrosion resistance. This technique can be implemented to enhance the durability of 316L-based implant materials in corrosive body environments, particularly in applications where long-term biocompatibility and surface stability are essential.